Application of visual design (or multimedia design) technologies in continuing design education - Brovchenko, Anatolii; Borysova, Tetiana; Pryhodii, Alla; Savenko, Ihor; Tymenko, Volodymyr (Convergências (Castelo Branco, Portugal), 2024)
The search for effective innovative approaches to teaching and developing students’ creative potential, as well as training qualified professionals who will meet the needs of a rapidly changing society, is a topical and prominent issue today. The purpose of the study was to thoroughly investigate and analyse the use of modern technologies in design education to strengthen the learning process and develop innovative methods and tools. The study used methods of analysis, synthesis, and a typological approach. As a result of this study, an in-depth analysis of the role of visual design technologies in the context of design education was performed. It was established that modern visual design technologies have significant potential to improve the quality and efficiency of the educational process in the field of design. The study found that the use of modern visual design technologies creates new opportunities for students, including the ability to experiment with unique design ideas and concepts, interact with virtual objects and receive instant feedback. This approach promotes active learning, stimulates creativity, and the development of critical thinking in students. The study also revealed modern views on design education, which indicate constant changes and trends in this field. It was found that design education and multimedia technologies support the development of creative thinking, promote innovation, and interdisciplinary communication. This study confirms the importance of applying visual design technologies in design education and reveals the prospects for the development of this industry in the modern world. The findings of this study can be used to develop updated approaches to teaching in continuing design education. The results obtained can serve as a basis for improving training programmes and developing new methods and tools.